Experimental and numerical analysis of penetration/removal response of endodontic instrument made of single crystal Cu-based SMA: comparison with NiTi SMA instruments. (7th March 2017) - Vincent, M; Xolin, P; Gevrey, A-M; Thiebaud, F; Engels-Deutsch, M; Ben Zineb, T
Abstract: This paper presents an experimental and numerical study showing that single crystal shape memory alloy (SMA) Cu-based endodontic instruments can lead to equivalent mechanical performances compared to NiTi-based instruments besides their interesting biological properties. Following a previous finite element analysis (FEA) of single crystal CuAlBe endodontic instruments (Vincent et al 2015 J. Mater. Eng. Perform . 24 4128–39), prototypes with the determined geometrical parameters were machined and experimentally characterized in continuous rotation during a penetration/removal (P/R) protocol in artificial canals. The obtained mechanical responses were compared to responses of NiTi endodontic files in the same conditions. In addition, FEA was conducted and compared with the experimental results to validate the adopted modeling and to evaluate the local quantities inside the instrument as the stress state and the distribution of volume fraction of martensite. The obtained results highlight that single crystal CuAlBe SMA prototypes show equivalent mechanical responses to its NiTi homologous prototypes in the same P/R experimental conditions.